Diplomasi Nabi Muhammad SAW Membawa Kejayaan Umat - Muqoddam Cholil (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
Prophet Muhammad was a messenger of God, human beings are God's perfect moral character. The last prophet sent by God to the world to give guidance and direction for mankind. He is the epitome of good character and become an idol for the whole human figure not only for Muslims but also for people generally. That is one of the relevance of the word of God which states that the Prophet Muhammad was sent as a mercy to all the worlds (Sura Al-Anbiya 21: 107). The term means a perfect man, he has a multidimensional behavior and equipment in various fields. She is a model and an example for all the goodness of humanity, one of the Prophet's ability is prominent in the field of diplomacy with men in all levels. In this paper the author tries to present examples of diplomacy Prophet Muhammad to mankind in general, whether hostile or his friends alone. We will look at the ability of the Prophet Muhammad in their face.